(untitled) (Medical Forum Monthly, 2020)
Objective: To assess the autologous blood injection in the treatment of recurrent temporomandibular joint dislocation Study Design: Randomized control clinical trial Place and Duration of Study: This study was conducted at the Oral and Maxillofacial Department Gajju Khan Medical College, Bacha Khan Medical Complex, Swabi from March 2019 to March 2020. Materials and Methods: Fifteen patients with bilateral recurrent dislocation were selected. Bilateral arthrocentesis was performed which was then followed by 2ml of autologous blood injection into the joint space tand 1ml injection into the pericapsular area. Postoperative evaluation was gone by history and physical examination for rate of recurrence, maximal mouth opening, frequency of laxation and complications. Results: Seven patients were male and 8 patients were female. Twelve (80%) patients had successful outcome with no dislocation and no further treatment was required while in 3(20%) patients there was recurrent dislocation. Conclusion: Autologous blood injection for the treatment of recurrent temporomandibular joint dislocation is simple, safe and effective procedure. With good patient’s compliance we recommend the use of autologous blood injection in the treatment of recurrent dislocation especially before going for more invasive procedures for correction.